Meningkatkan Literasi Digital di Sekolah Menengah Atas: Tantangan, Strategi dan Dampaknya pada Keterampilan Siswa - Sena Kurniawan; Yuni Siti Sarah (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Digital literacy has become an essential skill for high school students to face the challenges posed by an increasingly connected and digitized society. The aim of this research is to investigate the level of digital literacy among high school students, identify the issues they encounter, and develop a useful teaching approach to enhance digital literacy. This research employs a combination of quantitative and qualitative approaches. Researchers conducted surveys using questionnaires and interviews on digital literacy to assess the students' level of digital literacy. The results indicate that most students have a good understanding of digital technology, but there are some issues, such as digital ethics and information evaluation. We conducted interviews and focused group discussions to identify student challenges, such as digital security and the spread of misinformation. Based on the research findings, we propose an integrated teaching strategy to be incorporated into the school curriculum. This strategy includes teacher training in digital literacy, collaboration with libraries to improve research skills, and the integration of digital literacy into various subjects. We hope that by implementing this strategy, students will develop critical thinking, analytical, and ethical skills necessary for success in their daily lives.